2019
DOI: 10.1186/s12964-019-0322-x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose radiation regulates BRAF-induced thyroid cellular dysfunction and transformation

Abstract: BackgroundThe existence of differentiated thyroid cells is critical to respond radioactive iodide treatment strategy in thyroid cancer, and loss of the differentiated phenotype is a trademark of iodide-refractive thyroid disease. While high-dose therapy has been beneficial to several cancer patients, many studies have indicated this clinical benefit was limited to patients having BRAF mutation. BRAF-targeted paired box gene-8 (PAX8), a thyroid-specific transcription factor, generally dysregulated in BRAF-mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Bibby et al reported that silencing miR-330-5p increases MMP1 expression and promotes an invasive phenotype in esophageal adenocarcinoma [ 22 ]. It is also found that loss of miR-330-5p leads to PAX8 upregulation by LDR and suppression of thyroid carcinogenesis [ 23 ]. However, the biological functions and potential molecular mechanisms of miR-330-5p in the proliferation and metastasis of TC remain to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Bibby et al reported that silencing miR-330-5p increases MMP1 expression and promotes an invasive phenotype in esophageal adenocarcinoma [ 22 ]. It is also found that loss of miR-330-5p leads to PAX8 upregulation by LDR and suppression of thyroid carcinogenesis [ 23 ]. However, the biological functions and potential molecular mechanisms of miR-330-5p in the proliferation and metastasis of TC remain to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as reported by Lau et al [69], thiocyanate, an antioxidant related to the immune system, was increased in adults' saliva treated with low doses by cone beam computed tomography [105]. A low dose of 100 mGy γ-irradiation reduced BRAF V600E virus transformation of human thyroid normal follicular cells, and it also suppressed thyroid transformation in mice by restoring the thyroid metabolizing gene expression of PAX and, in addition, suppressed thyroid cancer carcinogenesis through inhibition of STAT3-miRNA-330-5p pathways [106]. As also seen by the previously reported low-dose IR effects on neoplastic transformation [107], the reduction of spontaneous lung cancers in mice [108], and immunogenic effects [109], typical low-dose hormetic effects exhibit beneficial outcomes.…”
Section: Hormesismentioning
confidence: 98%
“…In a recent study, thiocyanate (SCN − ), a biomolecule that acts as a natural antioxidant in the immune system, was found to be increased in the saliva of 10 healthy orthodontic patients (age 12-17 years) subsequent to exposure to LDIR effective doses of 0.174-0.256 mSv, delivered during cone beam computed tomography (CBCT), inferring that LDIR may exert protective effects by activating the natural antioxidant system [54]. In addition, LDIR (0.1 Gy, γ-radiation) has also demonstrated a bio-positive effect in reducing the transformation of thyroid cancer cells by restoring the thyroid metabolising genes expression, PAX8 and suppressing thyroid cancer carcinogenesis by inhibiting STAT3-miR-330-5p pathways in both cells and a mouse model [55]. Moreover, other experimental studies have demonstrated that the hormetic effects of LDIR only occur in normal cells or tissues and not in malignant cells [56][57][58].…”
Section: Ldir-induced Hormetic Effectsmentioning
confidence: 99%